2014
DOI: 10.1098/rspb.2013.2605
|View full text |Cite
|
Sign up to set email alerts
|

How superdiffusion gets arrested: ecological encounters explain shift from Lévy to Brownian movement

Abstract: Ecological theory uses Brownian motion as a default template for describing ecological movement, despite limited mechanistic underpinning. The generality of Brownian motion has recently been challenged by empirical studies that highlight alternative movement patterns of animals, especially when foraging in resource-poor environments. Yet, empirical studies reveal animals moving in a Brownian fashion when resources are abundant. We demonstrate that Einstein's original theory of collision-induced Brownian motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
90
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 27 publications
9
90
1
Order By: Relevance
“…We use the notationr 2 M to represent mussel movement, which is modelled explicitly as random walks of individual mussels 13 . Statistical analysis of experimental movement trails revealed that the distances covered by the mussels during 1 min could be approximated by an exponential distribution 13,33 , where the frequency h of occurrence decreased with movement distance r; h(r, b) ¼ (1/b) exp( À r/b). Here, the scaling parameter b is a function of the densities of mussels in the neighbourhood.…”
Section: Methodsmentioning
confidence: 99%
“…We use the notationr 2 M to represent mussel movement, which is modelled explicitly as random walks of individual mussels 13 . Statistical analysis of experimental movement trails revealed that the distances covered by the mussels during 1 min could be approximated by an exponential distribution 13,33 , where the frequency h of occurrence decreased with movement distance r; h(r, b) ¼ (1/b) exp( À r/b). Here, the scaling parameter b is a function of the densities of mussels in the neighbourhood.…”
Section: Methodsmentioning
confidence: 99%
“…In our non-Markovian model, the role of the collision and repulsion rate γ ± is drastically changed. This term is responsible for the shift from the superdiffusive Lévy walk to diffusion as the density increases [39]. The nonlinear equations for the structural densities n + (x,t,τ ) and n − (x,t,τ ) can be written as…”
mentioning
confidence: 99%
“…Motivated by the recent experiments [19,39], we introduce microscopic mean-field kinetic equations in which we combine two key ingredients: (1) the turning rate that depends on alignment and collision interactions between individuals and (2) non-Markovian effects. The crucial problem here is how to incorporate nonlinear interactions into non-Markovian superdiffusion.…”
mentioning
confidence: 99%
“…We modelled the movement of individuals in correspondance to natural mussel movements, using a heavy-tailed step length distribution (a Lévy walk with l = 2; de Jager et al 2011), where steps are made in random directions and their lengths are drawn from a power law distribution. A mussel ends its step prematurely when it encounters a conspecific (de Jager et al 2014). In our model, mussels cooperate after (and not during) pattern formation; therefore the attachment of byssus threads does not impair mussel movement.…”
Section: Methods An Individual-based Model Of Self-organized Patterningmentioning
confidence: 99%